SPATIAL DATA PROCESSING TOOLS AND APPLICATIONS FOR BLACK SEA CATCHMENT REGION - Gorgan, Dorian; Bacu, Victor; Mihon, Danut; Rodila, Denisa; Stefanut, Teodor; Abbaspour, Karim; Cau, Pierluigi; Giuliani, Gregory; Giuliani, Gregory; Ray, Nicolas; Lehmann, Anthony (International Journal of Computing, 2014)
The enviroGRIDS project has developed and provides through the BSC-OS portal a set of tools, applications and platforms concerning with the processing of huge spatial data for the Black Sea catchment region. The paper highlights the main issues of interoperability between Geospatial and Grid infrastructures, and between different platforms supporting the Earth Science oriented tools and applications. The BSC-OS portal provides end user applications for spatial data management, hydrological model calibration, environmental scenario development and execution, workflow based satellite image processing, data reporting and scenarios visualization, and development of Earth Science oriented training materials.